Sustained biological control of the cassava mealybug Phenacoccus manihoti (Hom: Pseudococcidae) by Epidinocarsis lopezi (Hym.: Encyrtidae) in Nigeria - Hammond, W.N.O.; Neuenschwander, Peter (1990)
Following the successful introduction of Epidinocarsis lopezi (De Santis) for biological control of the cassava mealybug (CM) Phenacoccus .manihoti Mat.-Ferr. in southwestern Nigeria in 1981 and 1982, 11 groups of cassava fields were sampled every 2 weeks up to 1988 for impact assessment. After 1984, CM populations remained mostly below 10 per tip despite the presence of native hyperparasitoids, demonstrating the long-term success of biological control by E. lopezi in the region. Indigenous polyphagous coccineilids were found only during peak host densities, whereas the specific E. lopezi was common throughout the year. During some periods, percentage parasitism indicated delayed density dependence. Since 89 % of all sampled cassava tips had no CM at all and the parasitisme is very mobile, parasitization rates were also calculated for individual infested tips (N = 4,878). Parasitism increased slightly with host density on tips having between I and 10 CM of the 3 rd and 4 th instars, indicating positive density dependence. Such tips comprised 64 % of all infested tips. At higher host densities, parasitism rates fell rapidly. The results are discussed in view of different theories on population regulation by biological control agents.